2021
DOI: 10.1111/nuf.12579
|View full text |Cite
|
Sign up to set email alerts
|

Primary care nurse practitioner burnout and perceptions of quality of care

Abstract: Background Burnout threatens patient care and clinicians are experiencing challenges within the practice environment. Little is known about nurse practitioner (NP) perceptions of burnout and its relationship to care quality and practice environment. We investigate the relationship between primary care NP burnout on perceptions of care quality and if the practice environment moderates the relationship between burnout and care quality. Methods This is a secondary analysis of cross‐sectional survey data from 396 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
2
11
0
1
Order By: Relevance
“…In the given period the mental health of the healthcare personnel is especially important for the society as a whole. Firstly, because it has a decisive effect on the quality of health services as mentioned in several studies [ 45 ] and, secondly, because it can affect the relationship of public trust in the healthcare system; a factor particularly important in ending the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the given period the mental health of the healthcare personnel is especially important for the society as a whole. Firstly, because it has a decisive effect on the quality of health services as mentioned in several studies [ 45 ] and, secondly, because it can affect the relationship of public trust in the healthcare system; a factor particularly important in ending the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout is a common phenomenon among healthcare professionals. Recent studies estimate that 25.3%-33.3% of healthcare workers suffer from burnout [ 20 , 23 , 24 ]. Likewise, clinician burnout has been a critical issue for the healthcare system as it has elicited several negative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, clinician burnout has been a critical issue for the healthcare system as it has elicited several negative outcomes. For instance, it has been proven that burnout not only had negative effects on job satisfaction [ 14 , 25 ] but also related to lower quality of care [ 23 ] and a higher likelihood of NPs intention to leave [ 24 ]. Additionally, several studies also found a negative influence of burnout on job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os profissionais de saúde, burnout e estresse ocupacional têm sido cada vez mais reconhecidos como ameaças consideráveis tanto para segurança do paciente (Soósová, 2021) quanto para a qualidade do atendimento (Abraham et al, 2021). Em função disso, a SB foi incluída na décima primeira revisão da Classificação Internacional de Doenças (CID-11), sendo um problema relacionado ao emprego ou desemprego, resultante do insucesso na gestão do estresse crônico presente no local de trabalho (World Health Organization, 2019).…”
Section: Introductionunclassified